Opportunities to Improve the Efficiency of Production and Processing of Livestock Products - Toshpulatova Kamola; Aliqulov Abdimumin Ismatovich (International Journal on Orange Technologies, 2022)
The theoretical practical and significance of the results of the study lies in the fact that they can serve as a basis for further development of the methodology for evaluating the monitoring of the functioning of livestock industries, including dairy cattle breeding in the format of studying a system of indicators, individual coefficients, as well as factors affecting the growth of the efficiency of agricultural production.